Pengembangan Bahan Ajar Berbasis Android Menggunakan Appy Pie pada Pembelajaran IPA Terintegrasi Ayat Al-Qur’an Materi Panas dan Perpindahannya - Widia Ratnasari; Maslikhah Maslikhah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This study aims to develop Android-Based Teaching Materials Using Appy Pie in Integrated Science Learning from Al-Qur'an Verses of Heat and Transfer. The type of research used is Research and Development (R&D) with the research subjects being teachers and students of MI Salatiga City. Data collection instruments used questionnaires, interviews, tests, and documentation.The process of developing teaching materials in this study uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The product is developed according to the needs analysis then tested for feasibility and revised until it is feasible to be implemented in learning. The results of the feasibility test / validation from media experts get an average percentage of 93.7% or a score of 3.75, science material experts as much as 89.2% or a score of 3.6, and interpreters as much as 88.3% or a score of 3.5. Based on the results of each validator, it shows that android-based teaching materials using Appy Pie in integrated science learning are verses of the Qur'an, heat material and its transfer are feasible to use. The effectiveness of Android-based teaching materials using Appy Pie in integrated science learning of verses of the Koran heat material and its transfer is shown from the results of the calculation of the t test on the students' pretest and posttest scores. The results of Paired Samples Statistics show the t-count value of 0.000 < 0.05, then Ha is accepted and Ho is rejected. There is a significant difference between the pretest and posttest data, so it can be concluded that the development of android-based teaching materials using Appy Pie in integrated science learning of al-Qur'an verses heat material and its transfer is effective for improving student learning outcomes in class V MI City of Salatiga.